A Framework for Reengineering AMPLIA Enviroment - Barros, Paulo Ricardo M.; Erhardt, Elton; Bez, Marta R.; Cazella, Sílvio César; Flores, Cecilia D. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2011)
The AMPLIA – Probabilistic Multiagent Learning Environment is an educational tool aimed at creating an additional resource for assistance to medical education, supporting the development of diagnostic reasoning. The first version has some limitations when it comes to access only local network (LAN) as a function of applied technologies, and provide students with an unfriendly interface. The proposed framework aims to enable the use of Internet resources, and to propose an interface for a computer game, we developed a new technology framework that will enable the provision of knowledge to other university.